An Efficient Diffusion Scheme for Chaos-Based Digital Image Encryption. (31st March 2014) - Chen, Jun-xin; Zhu, Zhi-liang; Zhang, Li-bo; Fu, Chong; Yu, Hai
Abstract : In recent years, amounts of permutation-diffusion architecture-based image cryptosystems have been proposed. However, the key stream elements in the diffusion procedure are merely depending on the secret key that is usually fixed during the whole encryption process. Cryptosystems of this type suffer from unsatisfactory encryption speed and are considered insecure upon known/chosen plaintext attacks. In this paper, an efficient diffusion scheme is proposed. This scheme consists of two diffusion procedures, with a supplementary diffusion procedure padded after the normal diffusion. In the supplementary diffusion module, the control parameter of the selected chaotic map is altered by the resultant image produced after the normal diffusion operation. As a result, a slight difference in the plain image can be transferred to the chaotic iteration and bring about distinct key streams, and hence totally different cipher images will be produced. Therefore, the scheme can remarkably accelerate the diffusion effect of the cryptosystem and will effectively resist known/chosen plaintext attacks. Theoretical analyses and experimental results prove the high security performance and satisfactory operation efficiency of the proposed scheme.